Effect of Statins on Major Adverse Cardiovascular Events in Patients with Coronary Artery Spasm: A Meta-Analysis of the Asia Region - Tian-Jun Zhao; Duan Luo; Xi Jiang; Feng Tang; Hui Jiang (Cardiovascular Therapeutics)
Background. Whether statins can reduce major cardiovascular adverse events (MACE) in patients with coronary artery spasm (CAS) is controversial. And most of the relevant research to date has been conducted in Asia. Methods. We systematically searched electronic databases for studies on the effect of statins on MACE in patients with CAS in Asia and published up to September 2022. We included data on MACE in a statin therapy patient group and a no-statin therapy control group. We then evaluated the effect of statin therapy on MACE in patients with CAS in Asia by meta-analysis and trial sequential analysis (TSA). All statistical analyses were performed using Stata 16.0 software and TSA software. Results. A total of 10 studies (n=9333 patients) were included in the final analysis. Meta-analysis showed that the use of statins had a significant effect on MACE in CAS patients (with RR, 0.70; 95% CI, 0.49-0.99), and the sensitivity analysis further confirmed this finding. Subgroup analysis suggested that the correlation between statin therapy and reduced MACE endpoint was stronger in Japanese patients and patients followed up for more than 4 years. But our TSA results indicated that the available samples were insufficient and further research is needed. Conclusions. Our meta-analysis suggests that statin therapy can reduce MACE in patients with CAS in Asia, and the correlation between the two was stronger in Japanese patients and patients followed up for more than 4 years.